Modulation of HSP60 Expression by Virgin Coconut Oil and Folic Acid in a Rotenone-Induced Zebrafish Stunting Model - AINI, SYAHANA; Ardiana, Hanida Aisyah; Emiliana, Farica; Nurdiana, Nurdiana; Ariani, Ariani; Corebima, Brigitta Ida Resita Vebrianti (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Stunting is characterized by impaired linear growth resulting from long term nutritional inadequacy and exposure to adverse environmental conditions. Mitochondrial dysfunction and disrupted cellular stress responses contribute to stunting. Heat Shock Protein 60 (HSP60) is a mitochondrial chaperone involved in proteostasis and reflects alterations in cellular stress regulation. This study evaluated the effects of VCO and folic acid on HSP60 expression in a rotenone-induced zebrafish model of stunting. A post-test only control group experiment included 450 zebrafish embryos assigned to five groups: NC, rotenone control, VCO, folic acid, and combination treatment. Treatments were administered from 2-72 hpf. HSP60 expression was quantified by RT-qPCR at 9 dpf using the 2^-ΔΔCt method. Group differences were analyzed using one-way ANOVA with Tukey's HSD as the post hoc test. Significant differences in HSP60 expression were observed among groups (p<0.001). Compared with NC, the rotenone group showed lower HSP60 expression, while all interventions further reduced expression, with the combination group showing the lowest level (0.13±0.04). These findings indicate that rotenone affected HSP60 expression, which may reflect changes in mitochondrial stress adaptation. VCO and folic acid were associated with additional modulation of Hsp60 expression, which may reflect altered cellular stress adaptation mechanisms.